Can Linguistic Theory Contribute to Linguistic Reconstruction? Case studies from Dogon. - (:unkn) unknown (My University, 2025)
Dogon is a small yet varied language family of central Mali which was undocumented before the 20th century. In the last two decades however, 20+ languages within the family have been sufficiently described to allow for the reconstruction of Proto-Dogon, the hypothesized ancestor of existing Dogon languages which, in relation to other West-African language, present surprising typological traits in their phonology (treatment of ND clusters, front/back harmony), morphology (lack of noun-classes) and syntax (V final). In this talk I will present a state of the art of Proto-Dogon phonology and discuss how issues of underlying vs surface forms and synchronic vs. diachronic phonology impact linguistic reconstructions. General issues of representation and change in Dogon will also be discussed. By focusing on the reconstruction of three core vocabulary items, ‘person’, ‘tooth’ and ‘iron’, with postulated metathesis of the initial syllable *NiCV → iNCV, we demonstrate how autosegmental theory may enhance the toolkit of the historical phonologist.
Keywords: African Research